Analisis Konsep Matematika Dalam Penyusunan Laporan Keuangan Mahasiswa Akuntansi - Vuvut Selviana; Ilham Saiful Fauzi; Zainal Abdul Haris; Fitrotul Maulidiyah (Mandalika Mathematics and Educations Journal, 2025)
Financial statements are a fundamental element of accounting and serve as the basis for strategic decision-making, requiring mastery of accounting principles and quantitative skills. This descriptive qualitative study aims to describe the mathematical concepts and their applications in the preparation of financial statements by accounting students. Data were collected through interviews, student grades, and financial statement documents. The results indicate that the essential mathematical concepts include basic arithmetic, algebraic equations (e.g., ), ratios/percentages, basic statistics, and rounding. Although all students employed the same concepts, the depth and level of integration varied. Students categorized as “very good” demonstrated the ability to link calculations with transaction reasoning, analyze ratios across periods, apply statistical tools for diagnosis, and maintain accuracy control, resulting in financial reports that are meaningful and actionable. In contrast, students in the “fair” category tended to be procedural, focusing on numerical accuracy but lacking interpretation of the underlying meaning. It is therefore recommended that mathematics instructors develop learning models that integrate mathematical theory with direct accounting practice. Project-based or real case study approaches can help students better understand the relationship between mathematical computation and the actual outcomes of financial reporting.